‫أﺛﺮ‬‫اﻟﺘﻮزﻳﻊ‬ ‫ﻋﻠﻰ‬ ‫اﻷداء‬ ‫ا‬ ‫ﻟﺘﺴﻮﻳﻘﻲ‬‫ﻓﻲ‬ ‫اﻟﻤﺆﺳﺴﺔ‬ ‫دراﺳﺔ‬‫ﺣﺎﻟﺔ‬ ‫ﻣﻠﺒﻨﺔ‬ ‫ﺑﻬﻴﺠﻲ‬ ‫ﺑﻌﻴﻦ‬ ‫ﺳﻨﻮر‬ ‫‪‬‬‫ﺳﻮق‬ ‫أﻫﺮاس‬ ‬‬ - ‫أﻣﺒﺎرك ‫ﺟ‬‫ﻤﺎل‬‫ اﻟﺼﻐﻴﺮ‬ ‬; ‫إﺑﺮاﻫﻴﻢ ‫ﻣﺼﻄﻔﻰ‬‫ﻣﺤﻤﺪ‬ ‬ (My University, 2017)
Summary: The study aims at identifying the effect of the distribution on the marketing performance in the organization which is represented by a set of indicators (market share, profitability, customer satisfaction). The sample was represented by workers of Bahiji Hassan al-Din in Ain Senour market, Using the questionnaire as a data collection tool, we distributed 20 questionnaires on the sample of the study. We used the descriptive analytical method to test hypotheses using the statistical program (SPSS 22) and also Excel program due to the nature of Some questions. This study found the importance of the elements of the marketing mix, especially the distribution component, and the importance of the marketing performance measured by the set of special indicators. We also found that the distribution does not have a strong impact on the marketing performance in the organization (dairy) We have reached some suggestions, the most important of which is to benefit from the experience of the institutions that preceded it in this field of service, and try to compare its performance with the performance of this institution to discover the strengths and weaknesses, and the reasons for their success or failure to achieve the desired goals.